2015
DOI: 10.1007/s40265-015-0436-4
|View full text |Cite
|
Sign up to set email alerts
|

Eluxadoline: First Global Approval

Abstract: Eluxadoline (Viberzi(™)), developed by Actavis (now Allergan), is an orally administered, first-in-class compound that functions as both a µ-opioid receptor agonist and a δ-opioid receptor antagonist, and is indicated for the treatment of diarrhoea-predominant irritable bowel syndrome (IBS-D) in adults. The agent was originally developed by Janssen Pharmaceutica. Eluxadoline has been approved in the US, and submissions to other global authorities are being contemplated or planned. This article summarizes the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…IBS-D is commonly characterized by pain and diarrhea, and eluxadoline was developed with a view to address both these symptoms. 20 , 28 Eluxadoline is an amino acid amide with a molecular weight of 569.65 g/mol and a molecular formula of C 32 H 35 N 5 O 5 ; 5-[[[(2S)-2-amino-3-[4-(aminocarbonyl)-2,6-dimethylphenyl]-1-oxopropyl][(1S)-1-(4-phenyl-1H-imidazol-2yl)ethyl]amino]methyl]-2-methoxybenzoic acid ( Figure 1 ).…”
Section: Eluxadoline and The Gut Opioid Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…IBS-D is commonly characterized by pain and diarrhea, and eluxadoline was developed with a view to address both these symptoms. 20 , 28 Eluxadoline is an amino acid amide with a molecular weight of 569.65 g/mol and a molecular formula of C 32 H 35 N 5 O 5 ; 5-[[[(2S)-2-amino-3-[4-(aminocarbonyl)-2,6-dimethylphenyl]-1-oxopropyl][(1S)-1-(4-phenyl-1H-imidazol-2yl)ethyl]amino]methyl]-2-methoxybenzoic acid ( Figure 1 ).…”
Section: Eluxadoline and The Gut Opioid Systemmentioning
confidence: 99%
“… 19 , 29 31 It has poor oral bioavailability and is used for its local effects at opiate receptors in the gastrointestinal tract. 20 Eluxadoline is a schedule IV drug in the US, subject to control under the Federal Controlled Substances Act of 1970, in the same class with tramadol and benzodiazepines. 20 , 28 …”
Section: Eluxadoline and The Gut Opioid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies in healthy volunteers found that a single oral dose of eluxadoline was poorly absorbed, with the drug being excreted primarily through the feces and with no identifiable metabolites in the urine . Low levels of eluxadoline have also been found in the hepatic portal vein in nonclinical studies, and clinical data suggest that eluxadoline is cleared primarily by OATP1B1‐mediated hepatic uptake and subsequent biliary excretion without significant hepatic metabolism …”
Section: Discussionmentioning
confidence: 99%
“…FDA‐approved therapies for adults with IBS‐D include eluxadoline, rifaximin, and alosetron (specifically for women with severe IBS‐D) . Eluxadoline (Viberzi; Furiex Pharmaceuticals, Inc, a subsidiary of Allergan plc, Parsippany, New Jersey) is a mixed μ‐opioid receptor and κ‐opioid receptor agonist and δ‐opioid receptor antagonist that is locally active in the gastrointestinal tract . In 2 phase 3 clinical trials, eluxadoline 75 mg and 100 mg twice daily demonstrated efficacy in improving the abdominal pain and stool consistency associated with IBS‐D, measured by a composite efficacy end point combining stool consistency and abdominal pain responses .…”
mentioning
confidence: 99%